2020
DOI: 10.1038/s41598-020-77941-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and functional characteristics of circulating and bone marrow PD-1- and TIM-3-positive T cells in treated multiple myeloma patients

Abstract: The aim of the present work was to evaluate counts and functional properties of PD-1+ and TIM-3+ T cells in peripheral blood (PB) and bone marrow (BM) of multiple myeloma (MM) patients following the induction therapy. Sixty patients were enrolled in the study, CD4+ and CD8+ T cells expressing PD-1 and TIM-3, intracellular production of IFNγ and intracellular expression of Granzyme B were assessed. Relative counts of the majority of circulating PD-1+, TIM-3+ and PD-1+TIM-3+ T cells were higher in MM patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
3
8
0
4
Order By: Relevance
“…The deficit in the Th1 type response observed in our study is likely associated with tumor progression, as we observed that patients with refractory advanced MM exhibited the lowest Th1 cell level and Th1/Treg ratio. The impact of the treatment-induced increase in PD-1 level on the compromised Th1/Treg ratio observed in the present study is consistent with recent observations [35] and may reflect the deterioration of T-cell-tumor immunity despite the treatment. Nonetheless, normalization of checkpoint levels on CD4 T cells in treated patients, despite development of refractoriness, appears to open an avenue for the reactivation of the immune responses after therapeutic use of checkpoint inhibitors in the combined modality.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The deficit in the Th1 type response observed in our study is likely associated with tumor progression, as we observed that patients with refractory advanced MM exhibited the lowest Th1 cell level and Th1/Treg ratio. The impact of the treatment-induced increase in PD-1 level on the compromised Th1/Treg ratio observed in the present study is consistent with recent observations [35] and may reflect the deterioration of T-cell-tumor immunity despite the treatment. Nonetheless, normalization of checkpoint levels on CD4 T cells in treated patients, despite development of refractoriness, appears to open an avenue for the reactivation of the immune responses after therapeutic use of checkpoint inhibitors in the combined modality.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, increased expression of inhibitory receptors PD-1, CTLA, LAG-3, and TIM-3, together with defective effector functions, is regarded as a hallmark of T cell exhaustion [25,26,28]. The influence of MM therapy on quantitative and functional characteristics of circulating CD4 T cells has consistently been reported by Batorov et al [35]. While it has been found that in the course of MM T cell exhaustion occurs predominantly in the myeloma BM, PB T cells also exhibit an abrogated function, albeit to a minor extent [5,25].…”
Section: Discussionmentioning
confidence: 85%
“…Batorov et al reported significantly higher levels of PD1+CD4+T cells, PD1+CD8+T cells, CD4+T cells, and CD8+T cells in multiple myeloma patients compared to healthy donors 25 , On the contrary, Sponaas et al did not detect any difference of PD1 expressed on CD8+T cells between myeloma patients and healthy controls, furthermore, high expression of PD1+CD8+T cells was not found to correlate with tumor load to suggest that these cells were specific for non-myeloma antigens 26 , our results came in alignment with Batorov et al with exception of CD4+ which was higher in healthy controls compared to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Batorov et al reported signi cantly higher levels of PD1+CD4+T cells, PD1+CD8+T cells, CD4+T cells, and CD8+T cells in multiple myeloma patients compared to healthy donors (25), On the contrary, Sponaas et al didn't detect any difference of PD1 expressed on CD8+T cells between myeloma patients and healthy controls, furthermore, high expression of PD1+CD8+T cells was not found to correlate with tumor load to suggest that these cells were speci c for non-myeloma antigens (26), our results came in alignment with Batorov et al with exception of CD4+ which was higher in healthy controls compared to patients.…”
Section: Discussionmentioning
confidence: 99%